Controllable, Self‐Powered, and High‐Performance Short‐Wavelength Infrared Photodetector Driven by Coupled Flexoelectricity and Strain Effect. Issue 7 (22nd May 2021) - Kumar, Mohit; Lim, Jaeseong; Park, Ji‐Yong; Seo, Hyungtak
Abstract: Mechanical deformation‐induced strain gradients and coupled spontaneous electric polarization field in centrosymmetric materials, known as the flexoelectric effect, can generate ubiquitous mechanoelectrical functionalities, like the flexo‐photovoltaic effect. Concurrently, nano/micrometer‐scale inhomogeneous strain reengineers the electronic arrangements and in turn, could alter the fundamental limits of optoelectronic performance. Here, the flexoelectric effect‐driven self‐powered giant short‐wavelength infrared (λ ≤ 1800 nm) photoresponse from centrosymmetric bulk silicon, indeed far beyond the fundamental bandgap (λ = 1100 nm) is demonstrated. Particularly, large on/off ratio (≈10 5 ), extremely high sensitivity (2.5 × 10 8 %), good responsivity of 96 mA W −1, decent specific detectivity of ≈1.54 × 10 14 Jones, and a rapid response speed of ≈100 µs, even at nanoscale (<30 nm), are measured at λ = 1620 nm. The infrared response sensitivity is tuned in a wide range (up to 1.4 × 10 8 %) by controlling the applied pointed force from 1 to 10 µN. These results confirm that emerging mechanoelectrical coupling not only sheds to achieve tunable optoelectronic performance beyond the fundamental limit, but also offers innovative numerous applications like mechanoptical switch, photovoltaic, sensors, and self‐driving vehicles. Abstract : Flexoelectric effect‐driven giant short‐wavelength infrared (λ ≤ 1800 nm) photoresponse from centrosymmetric bulk silicon (beyond fundamental bandgap, λ = 1100 nm) is demonstrated. Applied pointed force controllable infrared (λ = 1620 nm) sensitivity (up to 1.4 × 10 8 %), extremely high sensitivity (2.5 × 10 8 %), good responsivity of 96 mA W −1, and a rapid response speed of ≈100 µs, even at nanoscale (<30 nm), are reported.